Santri Character Education in Forming Personal Identity of Knowledgeable and Socially Ethical Muslims: (Case Study: Al Wasatiyah Islamic Boarding School, Dongkal, Cipondoh, Tangerang City) - Abdul Holik; Zainal Abidin; Euis Dewi Wijayanti (PT Mattawang Mediatama Solution, 2024)
Character education basically begins with instilling faith and moral education where the ultimate goal is the formation of a character for students who have an Islamic personality in the form of implementing social ethics in society. The characteristics of an Islamic personality referred to in the scope of this research are: upholding honesty, being disciplined, having manners, having knowledge of religion and science, having a soul and social ethics that are accepted in the environment. The superior programs of this Islamic boarding school are: study of the Yellow Book, Tahfidz Qur'an and Arabic. This Islamic boarding school has two dormitory buildings for male and female students with an average age of 13-18 years. Al Wasatiyah Islamic Boarding School also has general education facilities, There are: Madrasah Ibtidaiyyah, Middle and High School of Al Wasatiyah. The Al Wasatiyah Islamic Boarding School is located close to the Darul Qur'an Modern Islamic Boarding School, so that the religious and scientific nuances provided to the students are balanced so that it is hoped that it will be able to mold and realize the students' individuality into individuals with Islamic character and high social ethics. This character formation cannot be separated from the various programs implemented at the Al Wasatiyah Islamic Boarding School, namely